Diversity and Traditional Knowledge of Textile Dyeing Plants in Northeastern Thailand - Auemporn Junsongduang (2018)
© 2017, The New York Botanical Garden. The objective of this study was to document the traditional knowledge of plants used for textile dyeing by the Tai-Lao ethnic group in Roi Et province in northeastern Thailand. Traditional knowledge of plants used for textile dyeing is disappearing because of modernization including new lifestyles, urbanization, and the introduction of synthetic colors. Textile dyeing with local plants, however, is experiencing a revival connected to ecotourism and global interest in natural products. To exploit that potential, it is important to preserve the local knowledge related to textile dyeing. We interviewed 60 Tai-Lao informants in 15 villages and 9 districts about their dyeing traditions and the species used through individual semi-structured and focus groups interviews. A total of 56 species in 50 genera and 31 families were used for dyeing cotton and silks; most species belonged to Fabaceae (11 spp., 19%) and Anacardiaceae (5 spp., 9%). Trees (36 spp., 65%) were the best represented life form among the dye plants, followed by shrubs and herbs (8 spp., 16% each), and climbers (4 spp., 7%). Bark was the plant part most commonly used for dyeing (25 spp., 42%) followed by leaves (12 spp., 20%), and fruits (9 spp., 15%). Home gardens were the most common habitat of dye plant (30 spp., 53%) followed by community forests (16 spp., 28%). Indigofera tinctoria L. and Pterocarpus indicus Willd. were the most important dye plant species of the Tai-Lao ethnic group as demonstrated by their high use value index (UV = 0.60). Blue/indigo-blue was the color most informants had common knowledge about with an informant consensus factor (ICF) of 0.92 followed by black with ICF = 0.84. Ten different colors were obtained from the 56 plant species. Brown/pale-brown/golden-brown was the color obtained from most dye plant species (14 spp., 25%) followed by green/pale-green/dark-green (13 spp., 23%). Nine different kinds of mordants were used in the dyeing, including alum, chrome (potassium dichromate; K2Cr2O7), copper sulfate (CuSO4), iron oxide (Fe2O3), tamarind juice (tartaric acid), salt (NaCl), lime (calcium oxide; CaO), ash (potassium hydroxide; KOH), and mud. Among the 56 species used for textile dyeing, three are on the IUCN Red List of Threatened Species, including: Dipterocarpus alatus Roxb. & G.Don, Dipterocarpus obtusifolius Teijsm. ex Miq., and Pterocarpus indicus Willd. Documenting these and other species used for textile dyeing will provide additional arguments for their conservation. It will also help to secure the reappearing tradition of textile dyeing with local plants, and hence support the cultural integrity of the Tai-Lao communities, and serve as an example for other communities in Thailand and elsewhere for preserving their traditional knowledge.